Evaluation of Taxes and Revenues From the Energy Sector in the Baltics, Russia, and Other Former Soviet Union Countries - Gray, Dale. (Washington, D.C. : International Monetary Fund, 1998)
This paper examines the level and structure of fiscal revenues from the Baltics, Russia, and other former Soviet Union countries' (BRO) energy sector and suggests reforms in energy tax policy. Revenues from the oil and gas sectors are about half the level that might be expected from international comparisons. Low oil revenues result from infrastructure constraints on oil exports, weak tax administration, and inappropriate tax structures. Low gas revenues are due to low statutory tax rates, a tax structure that does not capture monopoly or resource rents, and weak tax administration. Taxation of oil products could be increased.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet